Classical cascade and sliding mode control tracking performances for a xy feed table of a high-speed machine tool. (17th October 2007) - Jamaludin, Z.; Brussel, H.V.; Swevers, J.
The development of robust tracking controllers for linear feed drive, high speed machine tools is the primary objective of this work. Robustness implies the controller ability to preserve tracking accuracy in the presence of cutting forces and friction forces. This paper discusses the design and tracking performances of traditional cascade and sliding mode controllers for a xy feed table. Tracking performances are analysed through circular tests that are performed at selected tracking speeds and circle radius. For cascade P/PI controller, tracking error is proportional to the reference speed and is inversely proportional to the velocity gain value of the position loop controller. Speed and acceleration feed forward further reduce this tracking error. Quadrant glitches, a product of non-linear friction phenomena at the point of velocity reversal, are observed. Sliding mode controller, however, significantly reduces quadrant glitches and exhibits greater dynamic stiffness while its tracking accuracy is comparable to the cascade controller.